2017
DOI: 10.15761/bhc.1000102
|View full text |Cite
|
Sign up to set email alerts
|

The proof and reasons that Starling’s law for the capillary-interstitial fluid transfer is wrong, advancing the hydrodynamics of a porous orifice (G) tube as the real mechanism

Abstract: Introduction and objective: In 1886, Starling proposed a hypothesis for the capillary-interstitial fluid (ISF) transfer, in which the capillary was thought a tube of a uniform diameter that is impermeable to plasma proteins. The flow of fluid across its wall was thought dependent upon a balance between the hydrostatic pressure within its lumen causing 'filtration', and the osmotic pressure of plasma proteins causing 'absorption'. The physical basis on which LP of a capillary was thought positive and responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 10 publications
1
64
0
Order By: Relevance
“…We then studied the porous orifice (G) tube akin to capillary and later enclosed it in a chamber (C), akin to interstitial fluid space, making the G-C apparatus demonstrating the G-C circulation phenomenon. The results of physical experiments was reported [18,19] but summarized here in order to facilitate the understanding of the results of physiological experiments reported here. The factors affecting the speed and efficiency of the G-C circulation were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…We then studied the porous orifice (G) tube akin to capillary and later enclosed it in a chamber (C), akin to interstitial fluid space, making the G-C apparatus demonstrating the G-C circulation phenomenon. The results of physical experiments was reported [18,19] but summarized here in order to facilitate the understanding of the results of physiological experiments reported here. The factors affecting the speed and efficiency of the G-C circulation were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…He confirmed the effectiveness of hypertonic 5% NaCl or 8.4% Sodium Bicarbonate both as anecdotal evidence [42] and in a prospective study [1,2] and also investigated the underlying faulty physiological law of Starling for the capillary interstitial fluid transfer [43,44]. The results of a career life investigation which aimed at quantifying volumetric gain and its relation to the TURP syndrome highlighting VOS are now reported.…”
Section: /8mentioning
confidence: 69%
“…The fact that the capillary is encircled at the inlet by the pre-capillary sphincter inspired the suggestion that it may induce a Venturi effect. Further studies have revealed the totally different roles of the arterial and venous pressures in regulating simulated capillary-interstitial fluid transfer [43,44]. In the light of these new findings, future studies are justified in order to explore the effects of volumetric overload on vascular pressures and tissue perfusion, as this may prove relevant to the pathogenesis of multiple organ failure and the adult respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…He confirmed the effectiveness of hypertonic 5% NaCl or 8.4% Sodium Bicarbonate both as anecdotal evidence [42] and in a prospective study [1,2] and also investigated the underlying faulty physiological law of Starling for the capillary interstitial fluid transfer [43,44]. The results of a career life investigation which aimed at quantifying volumetric gain and its relation to the TURP syndrome highlighting VOS are now reported.…”
Section: Introductionmentioning
confidence: 69%
“…The fact that the capillary is encircled at the inlet by the pre-capillary sphincter inspired the suggestion that it may induce a Venturi effect. Further studies have revealed the totally different roles of the arterial and venous pressures in regulating simulated capillaryinterstitial fluid transfer [43,44]. In the light of these new findings, future studies are justified in order to explore the effects of volumetric overload on vascular pressures and tissue perfusion, as this may prove relevant to the pathogenesis of multiple organ failure and the adult respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%